Surveying the current status of Vinh Long embankment structure by Georadar technology - Nguyen, Văn Giảng; Le, Ngọc Thanh; Wollny, Klaus; Nguyen, Bá Duẩn; Nguyen, Văn Công; Nguyen, Huy Vững (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Vinh Long embankment is an irrigation work built solidly to prevent erosion of Tien river bank for Vinh Long City. After a long time of use, on the surface of the embankment, there are observed subsidence positions. In order to properly assess the structural status of the embankment body below the ground, non-destructive georadar technology was used to survey the surface by Pulse Ekko 100A device with frequencies of 100 and 50 MHz antennas. The total length of the Georadar measurement profile is 500 m from the foot of Vinh Long bridge to the door of Cuu Long hotel and is divided into 5 subprofiles. Each sub-profiles with a length of 100 m was collected radar data with a measuring step of 0.25 m to build a radar cross-section and a structural section according to radar documentation using WinEKKO pro software. On the structural sections, there are radar anomalies related to defects in construction materials in the embankment body. The results of Georadar measurement and drawing show that some defects in the embankment body are not large but also need to be taken care of to increase the sustainability and aesthetics on the surface of Vinh Long embankment works.